Unusual Mott transition in multiferroic PbCrO3 - Wang, Shanmin; Zhu, Jinlong; Zhang, Yi; Yu, Xiaohui; Zhang, Jianzhong; Wang, Wendan; Bai, Ligang; Qian, Jiang; Yin, Liang; Sullivan, Neil S; Jin, Changqing; He, Duanwei; et al. (Proceedings of the National Academy of Sciences - PNAS, 2015)
The Mott insulator in correlated electron systems arises from classical Coulomb repulsion between carriers to provide a powerful force for electron localization. Turning such an insulator into a metal, the so-called Mott transition, is commonly achieved by "bandwidth" control or "band filling." However, both mechanisms deviate from the original concept of Mott, which attributes such a transition to the screening of Coulomb potential and associated lattice contraction. Here, we report a pressure-induced isostructural Mott transition in cubic perovskite PbCrO3. At the transition pressure of ∼3 GPa, PbCrO3 exhibits significant collapse in both lattice volume and Coulomb potential. Concurrent with the collapse, it transforms from a hybrid multiferroic insulator to a metal. For the first time to our knowledge, these findings validate the scenario conceived by Mott. Close to the Mott criticality at ∼300 K, fluctuations of the lattice and charge give rise to elastic anomalies and Laudau critical behaviors resembling the classic liquid-gas transition. The anomalously large lattice volume and Coulomb potential in the low-pressure insulating phase are largely associated with the ferroelectric distortion, which is substantially suppressed at high pressures, leading to the first-order phase transition without symmetry breaking.